2018
DOI: 10.4049/jimmunol.1701495
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses IL-1β Secretion and Prevents Inflammation through Inhibition of the NLRP3 Inflammasome

Abstract: Turmeric is traditionally used as a spice and coloring in foods. Curcumin is the primary active ingredient in the turmeric, and compelling evidence has shown that it has the ability to inhibit inflammation. However, the mechanism mediating its anti-inflammatory effects are not fully understood. We report that curcumin inhibited caspase-1 activation and IL-1β secretion through suppressing LPS priming and the inflammasome activation pathway in mouse bone marrow-derived macrophages. The inhibitory effect of curcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 43 publications
3
91
1
3
Order By: Relevance
“…The results were confirmed in vivo; it was demonstrated that administration of curcumin in SHR reduced intima-media thickness due to the inhibition of NF-κB and NLRP3 inflammasome and matrix metallopeptidase 9 (MMP-9) expression [70,71]. Yin et al showed that curcumin inhibited caspase-1 activation and IL-1β secretion through suppressing lipopolysaccharide (LPS) priming and NLRP3 inflammasome in mouse bone marrow-derived macrophages, and confirmed these results in vivo in a model of high-fat diet-induced insulin resistance in wild-type C57BL/6 mice [72]. Interestingly, in an in vitro study, Chen et al demonstrated that curcumin inhibits the M1 inflammatory phenotype of RAW264.7 macrophages as a result of the direct activation of the inhibitor protein κB-α (IkB-α) and polarizes the macrophages to become anti-inflammatory M2 phenotype through the activation of PPARγ [73].…”
Section: Introductionmentioning
confidence: 86%
“…The results were confirmed in vivo; it was demonstrated that administration of curcumin in SHR reduced intima-media thickness due to the inhibition of NF-κB and NLRP3 inflammasome and matrix metallopeptidase 9 (MMP-9) expression [70,71]. Yin et al showed that curcumin inhibited caspase-1 activation and IL-1β secretion through suppressing lipopolysaccharide (LPS) priming and NLRP3 inflammasome in mouse bone marrow-derived macrophages, and confirmed these results in vivo in a model of high-fat diet-induced insulin resistance in wild-type C57BL/6 mice [72]. Interestingly, in an in vitro study, Chen et al demonstrated that curcumin inhibits the M1 inflammatory phenotype of RAW264.7 macrophages as a result of the direct activation of the inhibitor protein κB-α (IkB-α) and polarizes the macrophages to become anti-inflammatory M2 phenotype through the activation of PPARγ [73].…”
Section: Introductionmentioning
confidence: 86%
“…Several studies showed that resveratrol and curcumin increase HO-1 expression in PC12 cells and endothelial cells, among other cell lines [168,170,172]. Moreover, it has been suggested that curcumin inhibits IL-1β secretion and NLRP3 inflammasome activation in macrophages, reduces soluble tau oligomers, and improves cognition by increasing HSP70, HSP90, and HSC70, in aged human tau transgenic mice [173,174].…”
Section: Redox Homeostasis and The Inflammatory Responsementioning
confidence: 99%
“…15,16 Multiple proteins and signalling pathways have been strongly linked to the modulation of NLRP3 inflammasome activation in macrophages. [17][18][19] Gong, T et al have summarized that NLRP3 phosphorylation modification regulates inflammasome assembly and activation by targeting different inflammasome components. 20 For instance, PKA specifically phosphorylates NLRP3 at Ser/Thr residue, which induces NLRP3 ubiquitination and the suppression of NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%